FASHION FORECASTER SEBAGAI PENENTU TREND - Nurbaeti Santika, Asri; Lutfia Zahra, Eneng (Universitas Negeri Jakarta, 2021)
This study aims to determine the competence of fashion forecasters as trend determinants with a sub focus on the concept of fashion forecasters and fashion forecaster analysis models. The method in this study uses a descriptive research method with a qualitative approach, the research instrument is the result of interviews with 5 sources consisting of lecturers and the Indonesia Trend Forecast team. The result of this research is that a fashion forecaster is someone who observes people's mindsets whose job descriptions carry out research and analysis that will be used by all groups as a trend reference. The analytical model used includes components such as economic, social, cultural, political and others. The process begins with a survey of data collection with experts, research, concept selection, translation and application.